The analysis of public policies: the evolution of a discipline and its relevance in Colombia (2017)
For several decades, the so-called public policy turn has become more relevant in the context of Latin America in general, and Colombia in particular. Both in the political and academic spheres, research projects or intervention have been put forward which, directly or indirectly, relate to a vague and general notion of "public policy." However, the advances in the specific field of the policy theory are timid. Therefore, it is necessary to deepen and energize the proper disciplinary debates of public policy, beyond the study of any policy in particular. Thus, this article explores the historical development of policy studies as an umbrella concept, and problematizes two different sub-fields -policy analysis and policy process research– to shed some light on the matter. Finally, the article concludes that despite difficulties and inconveniences while establishing definitive distinctions in this field, it is necessary to build some references to expand and maintain the dialogue between the workers within the different public policy fields.